AN ANALYSIS OF LEARNING STRESS LEVELS IN ONLINE AND DISTANCE LEARNING (ODL) AMONG FIRST AND SECOND YEAR TECHNICAL ENGINEERING STUDENTS DURING COVID -19 PANDEMIC - Siti Dewi Zatia Zahari; Salmah Anisah Abu Hasan; Sumaiyyah Omar (Universitas Duta Bangsa Surakarta, 2022)
The Covid-19 pandemic led to the closure of higher education institutions and the forced implementation of online learning in an attempt to reduce the spread of Covid-19. The lockdown and movement restrictions have changed students’ daily lives substantially and forced them to adjust to new norms in studying which increased concerns towards their stress levels. This research attempts to identify the perceived learning stress levels among first and second year students during the pandemic. Based on the convenience sampling approach, an online questionnaire adapted from the Perceived Stress Scale (PSS) and renamed as Perceived Learning Stress Scale (PLSS) was used to collect data from 113first and second year technical engineering students tto analyze their learning stress levels primarily from the impact of the online learning shift. Statistical Package for the Social Sciences (SPSS) software was used to analyze the learning stress scores and its relevance. The findings reveal that the majority of students experienced moderate to high level of learning stress and the presence of significant association between the semester of study and number of credit hours taken with the level of stress they experienced. Despite the study indicating that the students experienced stressful emotions due to learning platform shift, they also developed positive emotions such as confidence and ability to handle and control the learning problems and stress as they have adapted to the prolonged online learning conditions.